READY TO ADAPT TO NEW HABITS COVID-19 PANDEMIC INVOLVING HEALTH CADRES - Rusdianingseh Rusdianingseh (Caring : Jurnal Pengabdian Masyarakat, 2021)
Adaptation to New Habits is an act of implementing a new life order needed to maintain productivity during the COVID-19 pandemic by implementing transmission prevention behaviors or COVID-19 health protocols. This community service is an activity that aims to improve the knowledge and skills of health cadre in helping to improve family health by emphasizing the Adaptation of New Habits during the Covid-19 pandemic in the Kebonsari Surabaya. The COVID-19 pandemic has limited the activities of health cadre in the community so that it needs to be refreshed regarding health materials in the hope that through the health cadre, the adaptation of new habits during the covid-19 pandemic will be well socialized in the community. The method used in this community service activity is the provision of health education related to Adaptation to New Habits and a review of the skills of health cadre in providing health education to the community. The media used is a flipchart. The result of this community service activity is an increase in cadre knowledge by 30% regarding the material for adapting new habits during the covid_19 pandemic. Education through flipchart media is one way to increase knowledge.